Evaluating the Anti Microbial Effects of the Extract from 3 Plants (Thyme, Pennyroyal, Savory) On Spore Growth, Spore Elimination and Growth of Bacillus Cereus - Mehrdad Mimarian; Ali Toolabi; Ali Javadi; Khanjani Narges; Batol Jalalkamali (International Journal of Research in Chemistry and Environment (IJRCE), 2012)
The increased attention toward replacing chemical antimicrobials and anti oxidants with natural remedies has led to increased studies about plant derivatives and seeking natural plant extracts, in order to find a proper and natural substitute for chemical preservatives. To prove the preservative and anti-microbial characteristics of plant extracts, their effect on infectious bacteria and food decay has to be studied in laboratory and then real settings. In this study the effect of local Thyme, Pennyroyal and Savory in Qom Province on inhibition of Bacillus Cereus in nutrient broth environments with different essence concentrations (0.4, 0.8, 1.5, 2.5, 3, 3.5 and 4.5 μgr/ml) in different time intervals and different temperatures was evaluated. The percentage of grown and inhibited spores of this microorganism was determined by a hemocytometer with specific spore dyeing. Also the bacteria growth and the cell deformation was studied by a optic microscope and photos. The analysis of the three plants (Thyme, Pennyroyal and Savory) in this study was done by GC/MS. The extracts of Thyme and Savory in 37 degrees and in 0.4 and 0.8 μgr/ml concentration had a minimum inhibitory concentration (MIC) equal to 3 μgr/ml in inhibiting the growth of Bacillus Cereus, but had a MIC=3 μgr/ml on the growth and spore production of these bacteria after 48 hours. As can be seen in the extracts studied, the more deterrent summer savory and thyme, and oregano extracts are then.